Emergency reversal of anticoagulation with a three-factor prothrombin complex concentrate in patients with intracranial haemorrhage - Imberti, Davide (Edizioni SIMTI — SIMTI Servizi Srl, 2011)
BACKGROUND: Intracranial haemorrhage is a serious and potentially fatal complication of oral anticoagulant therapy. Prothrombin complex concentrates can substantially shorten the time needed to reverse the effects of oral anticoagulants. The aim of this study was to determine the efficacy and safety of a prothrombin complex concentrate for rapid reversal of oral anticoagulant therapy in patients with intracranial haemorrhage. METHODS: Patients receiving oral anticoagulant therapy and suffering from acute intracranial haemorrhage were eligible for this prospective cohort study if their International Normalised Ratio (INR) was higher than or equal to 2.0. The prothrombin complex concentrate was infused at doses of 35–50 IU/kg, stratified according to the initial INR. RESULTS: Forty-six patients (25 males; mean age: 75 years; range 38–92 years) were enrolled. The median INR at presentation was 3.5 (range, 2–9). At 30 minutes after administration of the prothrombin complex concentrate, the median INR was 1.3 (range, 0.9–3), and the INR then declined to less than or equal to 1.5 in 75% of patients. The benefit of the prothrombin complex concentrate was maintained for a long time, since the median INR remained lower than or equal to 1.5 (median, 1.16; range, 0.9–2.2) at 96% of all post-infusion time-points up to 96 hours. No thrombotic complications or significant adverse events were observed during hospitalisation; six patients (13%) died, but none of these deaths was judged to be related to administration of the prothrombin complex concentrate. CONCLUSIONS: Prothrombin complex concentrates are an effective, rapid and safe treatment for the urgent reversal of oral anticoagulation in patients with intracranial haemorrhage. Broader use of prothrombin complex concentrates in this clinical setting appears to be appropriate.